Effects of alloxan on some blood parameters in dogs - Ali Muhtar Tiftik; Kürşat Turgut; Firuze Özeren (Eurasian Journal of Veterinary Sciences)
The effect of alloxan on some blood parameters of six alloxan diabetic dogs was investigated.